As operações mentais e a aprendizagem da física teórica - Brandão, Sonia Maria Miranda (1982)
The teaching of The PrincipIes of Physics in Junior High Schools within the state school system has proved inefficient in terms of getting the students understanding the physics taught at the senior High school leveI. This makes integration in to contemporary technological society rather difficult both in terms of access to jobs requiring specialized labor and/or to university. The principIes of modern science can and ought to be mobilized to solve this problem -the understanding of contemporary physics requires a well strutured mental frame because of its high leveI of abstraction. The epistemological genetics of Jean Piaget shows that the explanation of the physical environment begins at the very moment man gets in touch with reality. The structuring of reality becomes more and more complex in accordance with man's mental potencial and his interpretation of this reality. Reasoning takes place as a consequence of the operations that occur in our brain and this becomes possible due to the underlying mental structures. These structures develop as man interacts with the environment, allowing at the beginning a sensorimotor interaction, which gradually gets organized till it dominates the concrete operational stage. It then may even reach the formal operational stage which deals with abstract concepts -the latter is possible when the child has got to the age of adolescence. The PrincipIes of Physics taught at Junior High school leveI requires the understanding and the command of both the concrete and the formal operational though. A survey carried out among the two last grades of Junior High School students attending the second grade of a Teacher Trainning Course reveled that no one had not reached the complete control of the concret operations, as a result the learning of physics at this leveI is seriously impaired and there is a dire need to try to change the teacher's attitude toward students so that their mental potential can be activated and the teaching becomes more effective.